Ecological and evolutionary aspects of seed coat and seedling development in Juncus tenuis (Juncaceae, Poales) - Silva, Lucimara Reis de Oliveira [UNESP]; Oriani, Aline [UNESP] (Springer Nature, 2022)
This work aimed to understand ecological and evolutionary aspects of Juncus tenuis (Juncaceae) by analyzing its seed coat and seedling development. Mature seeds were germinated under controlled conditions and analyzed every 24 h for 60 days. Seeds and seedlings at different developmental stages were analyzed using a stereomicroscope, light microscopy, and scanning electron microscopy. The seed coat consists of the endotegmen, endotesta, and exotesta. The endotegmen is tanniferous, and the exotesta is mucilaginous. The germination percentage was low (28%), a result that may be related to specific light, humidity, and temperature requirements to overcome dormancy. Germination begins with the disruption of the seed coat and the emergence of a phaneromer, followed by the development of the collar rhizoids and the primary root. The anatomical analyses show that the formation of shoot and root apical meristems occurs only after the elongation of the phaneromer. The anatomy of the seedlings at early development is described for the first time for the family. The phaneromeric cotyledon is shared by Juncaceae and Thurniaceae and is most likely the ancestral condition in the cyperid clade (Poales). The presence of a mucilaginous exotesta is probably related to seed protection, dispersal, and germination.
Keywords: Cotyledon; Germination; Mucilaginous exotesta; Phaneromer; Seed coat